BIOACCUMULATION OF IRON (Fe) IN Bacillus JA1, Sporosarcina JA4, AND Lysinibacillus JB2 - Afianita Dian Rahmawati; Enny Zulaika (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Carbonatogenic bacteria are able to produce calcium carbonate (CaCO3). Steel reinforcement of concrete is mainly made of a mixture of carbon (C) and ferrous (Fe) elements. Fe is classified as heavy metal, when in high concentrations it is toxic to bacteria. The purpose of this study was to determine the bioaccumulation of carbonatogenic bacteria to Fe. The isolates used in this study were Bacillus JA1, Sporosarcina JA4, and Lysinibacillus JB2. All isolates were subcultured on nutrient agar slant media. Cultures were made on minimal salt medium: nutrient broth (95% : 5%) with 24 hours incubation. Bioaccumulation test using minimal salt medium: nutrient broth (95% : 5%) containing ferrous 5 ppm and 10 ppm. Accumulated ferrous concentration was measured using atomic absorption spectrophotometry. The result of this research is that the bioaccumulation of ferrous by the isolates after 2 hours of incubation is greater than 1 hour of incubation. Bacillus JA1 has the highest bioaccumulation ability which was 9,19 ppm after 2 hours exposure of 10 ppm ferrous and its ferrous bioaccumulation efficiency was 91,85%.